Respuesta :

Answer:

kindly using which rule?

Answer:

[tex]\boxed{\boxed{\sf x=\frac{\sqrt{217} +2}{3} }\:or\: {\sf\boxed{\sf x=\frac{2-\sqrt{217} }{3} } }}[/tex]

Step-by-step explanation:

[tex]\boxed{\sf Quadratic \:equation}[/tex]

*All equations of the form ax^2+bx+c=0 can be solved using the Quadratic Formula. *

[tex]\boxed{\sf \square \: \:\frac{-b\pm \sqrt{b^2-4ac}}{2a}}[/tex]

The Quadratic Formula gives two solutions, one when ± is addition and one when its subtraction.

________________________________

[tex]\boxed{\sf 3x^2-4x-71=0}[/tex]

This equation here is in the standard form: ax^2+bx+c=0.

Substitute 3 → a, -4 → b, -71 → c.

[tex]\sf x=\cfrac{-\left(-4\right)\pm \sqrt{\left(-4\right)^2-4\times \:3\left(-71\right)}}{2\times \:3}[/tex]

→ Square -4, and then multiply -4 × 3= :

[tex]x=\cfrac{-(-4)\pm \sqrt{16+12(-71)} }{2\times 3}[/tex]

Multiply -12 × -71 = 868, then Add 16+852= 868

[tex]\sf x=\cfrac{-(-4)\pm 2\sqrt{217} }{2\times 3}[/tex]

Take the Square root of 868 2√(217).

* the opposite of -4 → 4.

[tex]\sf x=\cfrac{4\pm 2\sqrt{217} }{2\times 3}[/tex]

Multiply 2 × 3 = 6

[tex]\sf x=\cfrac{4\pm 2\sqrt{217} }{6}[/tex]

Now, we'll solve the equation when ± is plus.

→ Add 4+ 2√(217).

→ Divide 4+ 2√(217 ) by 6.

[tex]\boxed{\sf x=\frac{\sqrt{217} +2}{3} }[/tex]

Now, we'll solve the equation when ± is minus.

→ Subtract 2√(217) from 4.

→ Divide 4 - 2√(217) by 6.

[tex]\boxed{\sf x=\frac{2-\sqrt{217} }{3} }[/tex]

_________________________________________

ACCESS MORE